PKM PENGEMBANGAN USAHA PENGOLAHAN PRODUK IKAN TONGKOL, SEBAGAI UPAYA MENINGKATKAN PENDAPATAN ISTRI NELAYAN DI DESA KATIALADA, KECAMATAN KWANDANG, KABUPATEN GORONTALO UTARA, PROVINSI GORONTALO - Putri Sapira Ibrahim (UPPM Politeknik Gorontalo, 2020)
Katialada Village is located in Kwandang sub-district, North Gorontalo District, Gorontalo Province. One of the dominant marine potentials in Katialada is Tuna. Based on the report from the North Gorontalo District Fisheries Service in 2016, the average catch of Tuna each month reached 300 tons. Bolowa and Cakalang SMEs (Small and Medium Enterprise) are a community business group consisting of fishermen's wives in Katialada Village established since 2014. Bolowa SMEs produce pickled products, while UKM Cakalang produces abon and panada tore cakes. Based on the information compiled from the Bolowa and Cakalang SME groups, there are several problems and obstacles that hamper the development of SME groups. These constraints and problems are limited equipment used, there is no taste diversification, unattractive product packaging, bad business management, and a marketing system that has not been maximized. To overcome those problems, the solution agreed with partners is the procurement of tools to drain the oil contained in the product, procurement of vacuum sealer tools to package the product, there are 5 variations of flavors which are divided based on the level of spiciness, the creation and design of products that are good and attractive, giving business management training to be better, finding partners to sell products, creating accounts on online buying and selling sites and social media as a marketing medium. The method used in the activity is lecture, discussion and practicum. In addition, the facilities support from the Gorontalo Polytechnic Machine and Agricultural Equipment Study Program in the form of workshops and food microbiology laboratories in the Agricultural Product Technology Study Program will support the implementation and success of the service program.